Directed Evolution of Proteins through In Vitro Protein Synthesis in Liposomes - Takehiro Nishikawa; Takeshi Sunami; Tomoaki Matsuura; Tetsuya Yomo (Journal of Nucleic Acids)
Directed evolution of proteins is a technique used to modify protein functions through “Darwinian selection.” In vitro compartmentalization (IVC) is an in vitro gene screening system for directed evolution of proteins. IVC establishes the link between genetic information (genotype) and the protein translated from the information (phenotype), which is essential for all directed evolution methods, by encapsulating both in a nonliving microcompartment. Herein, we introduce a new liposome-based IVC system consisting of a liposome, the protein synthesis using recombinant elements (PURE) system and a fluorescence-activated cell sorter (FACS) used as a microcompartment, in vitro protein synthesis system, and high-throughput screen, respectively. Liposome-based IVC is characterized by in vitro protein synthesis from a single copy of a gene in a cell-sized unilamellar liposome and quantitative functional evaluation of the synthesized proteins. Examples of liposome-based IVC for screening proteins such as GFP and β-glucuronidase are described. We discuss the future directions for this method and its applications.